Cropping systems and agricultural management strategies affect soil organic carbon dynamics in semi-arid regions - Gorooei, Aram; Aynehband, Amir; Rahnama, Afrasyab; Gaiser, Thomas; Kamali, Bahareh (Frontiers in Sustainable Food Systems, 2023)
Soil organic carbon (SOC) dynamic is one of the important factors that directly influence soil properties and quality. In agro-ecosystems, the SOC dynamics are strongly linked to agricultural management practices. This study investigated the response of SOC fractions to various combinations of agricultural management practices based on measurements obtained from an experiment conducted over four growing seasons from 2018 to 2020 in Ahvaz, Iran. The experimental treatments involved three agricultural strategies combined with four crop rotation systems. The agricultural strategies comprised conventional (CON: mineral fertilizer, removal of all crop residues, chemical weeding control), organic (ORG: organic fertilizer, 30% return of crop residues to the soil, mechanical weeding), and integrated (INT: mineral/organic fertilizer, 15% return of crop residues, chemical/mechanical weeding) strategies. The crop rotation systems were: fallow-wheat (F-W), corn-wheat (C-W), sesame-wheat (S-W), and mung bean-wheat (B-W). SOC, labile-C (here oxidizable carbon in 333 mM KMnO4-C), and non-labile-C were measured. After two years of experiment, no remarkable improvement was found in SOC of CON strategy. The ORG and INT strategies contained on average 1.1 and 1.06 times more SOC than the CON strategy, respectively. The value of labile-C was decreased during summer cultivations and increased in the soil samples collected after winter cultivations. However, although the quantity of labile-C in ORG was higher than INT and CON over time, after the second summer cultivation due to the gradual accumulation of organic matter and high levels of temperature and humidity, it had a lower content in ORG. In all three agricultural management strategies, the SOC content in the four rotation systems was according to the following descending order B-W > C-W > S-W > F-W. Therefore, for this region, M-W and S-W crop rotation systems are recommended in addition to C-W (which is the most common rotation system). However, crop rotation systems were more beneficial for C-sequestration when combined with organic/ inorganic fertilization and crop residue incorporation. This study gives promising results for implementing INT and ORG strategies under long-term cropping systems containing various summer crops in rotation with wheat for improving SOC dynamics and conserving soil quality in semi-arid regions in Iran.